The study of the “Cetus” unmanned aerial vehicle for topographic aerial surveying - Hlotov, Volodymyr; Hunina, Alla; Kolb, Ihor; Kolesnichenko, Vadim; Trevoho, Ihor (Geodesy and Cartography, 2021)
The work aims to analyze and study the possibilities of using “Cetus” unmanned aerial vehicle (UAV) for performing topographic aerial surveys. The authors developed and tested aircraft-type UAV for topographic aerial photography. The studies were conducted on a specialized landfill, at which there is an appropriate number of situational points whose coordinates are determined with high accuracy. These points were used as both reference and control points. The obtained UAV aerial survey materials were subjected to a phototriangulation process to determine the orientation elements and to analyze, first and foremost, the angular orientation elements. The surveying was carried out on a mountainous territory, where the spatial coordinates of 37 situational points were determined by the method of ground-based GPS survey with an average accuracy of up to 0.05 m. These points were used as reference and control points. Aerial photography was performed in such a way that the scale of the images was as uniform as possible.The design solutions implemented in the Cetus UAV provide all the possibilities to perform aerial surveys of territories in strict compliance with the projected flight parameters. UAV equipment provides the necessary real-time correction of the position of the aerial camera. At the same time the optimum straightness of routes, stability of scales and mutual overlapping of pictures is reached. Regarding the accuracy of obtaining the spatial coordinates of the points of terrain objects, using “Cetus” UAV surveys, plans can even be made on a scale of even 1: 1000. As a result of the creation of the UAV “Cetus”, it became possible to perform the topographic aerial survey of the territories and to create large-scale orthophotos that fully meet the instructions. As a result of testing the “Cetus” UAV, it can be used in production processes when drawing up topographic plans for a large-scale series: 1: 1000 – 1: 5000, which will significantly save the cost of performing topographic work.